Revolusi Industri 4.0 Dalam Penguatan Kesiapsiagaan Bencana Di Indonesia - Yuhdi Fahrimal; Muhammad Reza; Afrizal Tjoetra (Communication, 2019)
This paper aims to further examine the opportunities and challenges of the industrial revolution 4.0 in disaster preparedness management. The method used is qualitative by analyzing articles obtained from Google Scholar with keywords industrial revolution 4.0 and disaster preparedness. The results of an analysis of documents related to the industrial revolution 4.0 found that cloud computing technology, artificial intelligence, big data, and the internet of things are useful in collecting data, mapping, and design of disaster risk information in real time and up to date. These conditions make management of disaster management more effective and efficient because the data is presented accurately so as to minimize errors or data distortion. Challenges that may be faced in the integration of the industrial revolution 4.0 technology and disaster preparedness management are also discussed.